Variable frequency drive optimization using torque ripple control and self-Tuning PI controller with PSO - Mudundi Rekha; Malligunta Kiran Kumar (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Drive’s output power must be restricted for the prevention of stresses over higher components in the input power system while utilizing a three-phase Variable Frequency Drive (VFD) which has powered from a single-phase AC source. To resolve this problem, we introduced a novel motor q-axis current (M-QAC) with torque ripple control (TRC) of an induction motor and self-tuning PI controller with particle swarm optimization (STP-PSO) for mitigating the stress over induction motor by the torque ripple elimination and controlling. Our proposed approach has an information related to the different parts stresses of the VFD which includes the terminal block and the diodes in the input side, DC bus capacitors, torque ripple, harmonics in the current and active performance for sudden changes in the speed and load. Our proposed model is simulated in MATLAB/Simulink environment. In this  paper the standard dc-bus voltage ripple-based fold- back, q-axis average current fold-back and q-axis ripple current fold-back methods are utilized for the comparative analysis. Also the comparative analysis of proposed M-QAC, TRC and STP-PSO methodologies are provide with respect to steady-state values of peak-to-peak dc voltage (Vdc), peak-to-peak input current (IINPUT), input RMS current (IRMS), motor speed and the output power. Extensive simulated performance show that the STP-PSO obtained superior results over conventional standard dc-bus voltage ripple-based fold-back method, M-QAC and TRC schemes.